Complexity, Adaptation, and Results - Barder, Owen; Ramalingam, Ben (Center For Global Development, 2012)
In the last of a series of three blog posts looking at the implications of complexity theory for development, Owen Barder and Ben Ramalingam look at the implications of complexity for the trend towards results-based management in development cooperation. They argue that is a common mistake to see a contradiction between recognising complexity and focusing on results: on the contrary, complexity provides a powerful reason for pursuing the results agenda, but it has to be done in ways which reflect the context. In the 2012 Kapuscinski lecture Owen argued that economic and political systems can best be thought of as complex adaptive systems, and that development should be understood as an emergent property of those systems. As explained in detail in Ben’s forthcoming book, these interactive systems are made up of adaptive actors, whose actions are a self-organised search for fitness on a shifting landscape. Systems like this undergo change in dynamic, non-linear ways; characterised by explosive surprises and tipping points as well as periods of relative stability. If development arises from the interactions of a dynamic and unpredictable system, you might draw the conclusion that it makes no sense to try to assess or measure the results of particular development interventions. That would be the wrong conclusion to reach. While the complexity of development implies a different way of thinking about evaluation, accountability and results, it also means that the ‘results agenda’ is more important than ever.
Keywords: IMPORTANT

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen Barder explores the implications of complexity theory for development policy. He explains how traditional economic models have tried and failed to understand why some countries have managed to improve living standards while other countries have not.
Keywords: IMPORTANT